Inhibition Effect of Kinetic Hydrate Inhibitors on the Growth of Methane Hydrate in Gas–Liquid Phase Separation State - Liwei Cheng; Limin Wang; Zhi Li; Bei Liu; Guangjin Chen (Energies, 2019)
The effect of kinetic hydrate inhibitors (KHIs) on the growth of methane hydrate in the gas–liquid phase separation state is studied at the molecular level. The simulation results show that the kinetic inhibitors, named PVP and PVP-A, show good inhibitory effects on the growth of methane hydrate under the gas–liquid phase separation state, and the initial position of the kinetic hydrate inhibitors has a major effect on the growth of methane hydrates. In addition, inhibitors at different locations exhibit different inhibition performances. When the inhibitor molecules are located at the gas–liquid phase interface, increasing the contact area between the groups of the inhibitor molecules and methane is beneficial to enhance the inhibitory performance of the inhibitors. When inhibitor molecules are located at the solid–liquid phase interface, the inhibitor molecules adsorbed on the surface of the hydrate nucleus and decreased the direct contact of hydrate nucleus with the surrounding water and methane molecules, which would delay the growth of hydrate nucleus. Moreover, the increase of hydrate surface curvature and the Gibbs–Thomson effect caused by inhibitors can also reduce the growth rate of methane hydrate.